Frequent promoter hypermethylation associated with human papillomavirus infection in pharyngeal cancer. (28th October 2017) - Nakagawa, Takuya; Matsusaka, Keisuke; Misawa, Kiyoshi; Ota, Satoshi; Takane, Kiyoko; Fukuyo, Masaki; Rahmutulla, Bahityar; Shinohara, Ken-ichi; Kunii, Naoki; Sakurai, Daiju; Hanazawa, Toyoyuki; Matsubara, Hisahiro; et al.
Abstract: Oropharyngeal squamous cell carcinoma (OPSCC) incidence has increased dramatically due to human papillomavirus (HPV); however, associated epigenetic alterations are not well studied. We performed genome-wide DNA methylation analysis using an Infinium 450k BeadArray for clinical OPSCC and non-cancerous samples and cancer cell lines with/without 5-aza-2′-deoxycytidine and/or trichostatin A treatment. Frequent promoter hypermethylation and methylation-associated silencing were detected in 144 genes, which included those involved in cell-cell signaling and neuron differentiation. The methylation of nine genes ( GHSR, ITGA4, RXRG, UTF1, CDH8, FAN19A4, CTNNA2, NEFH, and CASR ) was quantitatively validated in 70 pharyngeal SCC cases by pyrosequencing. Hypermethylation significantly correlated with HPV-L1 positivity, but not with age or smoking status. p16 INK4A was generally activated in HPV-L1(+) tumors, and p16-positive cases significantly associated with better prognosis. RXRG hypermethylation strongly correlated with positivity of HPV-L1 and p16 ( P  = 3 × 10 −5 and P  = 5 × 10 −4, respectively). RXRG -methylation(+) significantly associated with better prognosis when analyzing all tumor cases ( P  = 0.04), and when analyzing the p16-negative poorer-outcome group ( P  = 0.03). Thus, aberrant DNA methylation might be involved in HPV-associated OPSCC; in addition, DNA methylation could serve as a marker to classify subgroups based on outcome. Highlights: Genome-wide analysis revealed genes frequently methylated and silenced in OPSCC. Aberrant DNA methylation might associate with HPV infection and OPSCC subgroup. Methylation might represent a marker to classify OPSCC subgroups based on outcome. RXRG methylation suggested to be used with p16 expression to predict OPSCC outcome.